2022
DOI: 10.3390/ijerph19095269
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Mental Health Literacy Curriculum among Undergraduate Public Health Students

Abstract: Mental health literacy (MHL) plays an important role in public health. Improving MHL can promote mental health at the individual and public levels. To date, no published studies have assessed the effectiveness of MHL curriculum interventions among undergraduate public health students. The participants in this study were undergraduate public health students (n = 48) who were enrolled in an 18-week MHL curriculum for 100 min per week. MHL was assessed using the Mental Health Literacy Scale for Healthcare Student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…However, the assessment scores do not fully map the mental process of internalizing their curriculum knowledge. The mental state measures individuals' motivation for learning the curriculum, their processing of the knowledge system, and their output methods from the perspective of psychological cognition, revealing the specific details of primary education teacher candidates' mental representations in the course of learning the curriculum and reflecting more objectively their mechanisms of constructing the curriculum knowledge system, and the findings are more consistent with the findings of other scholars (Lai et al, 2022;Wu et al, 2022). Mental state and academic achievement are two important dimensions for evaluating individuals' mastery and application of the curriculum knowledge system, and combining them will help to further explore the structure of individuals' internal and external mental representations for understanding problems or solving them, and to find the root causes of their cognitive difficulties.…”
Section: Discussionsupporting
confidence: 69%
“…However, the assessment scores do not fully map the mental process of internalizing their curriculum knowledge. The mental state measures individuals' motivation for learning the curriculum, their processing of the knowledge system, and their output methods from the perspective of psychological cognition, revealing the specific details of primary education teacher candidates' mental representations in the course of learning the curriculum and reflecting more objectively their mechanisms of constructing the curriculum knowledge system, and the findings are more consistent with the findings of other scholars (Lai et al, 2022;Wu et al, 2022). Mental state and academic achievement are two important dimensions for evaluating individuals' mastery and application of the curriculum knowledge system, and combining them will help to further explore the structure of individuals' internal and external mental representations for understanding problems or solving them, and to find the root causes of their cognitive difficulties.…”
Section: Discussionsupporting
confidence: 69%
“…For example, MHL training (such as Mental Health First Aid; Kitchener & Jorm, 2002) that contains antistigma and enhancement of self-efficacy can increase the likelihood of seeking professional help among medical and nursing students (Bond et al, 2015) and should be included in the curricula for health care students (Pham et al, 2014). H. J. Lai et al (2022) have indicated that a school-based curriculum with comprehensive coverage of MHL components could raise help-seeking attitudes in public health students.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our findings indicate a greater need for psychoeducational campaigns and interventions to improve knowledge of mental health in young Greek people in relation to their peers from Australia and the UK. For instance, there are educational interventions, both in live presence [78] and digital [79], that enable students to continuously acquire knowledge related to mental health, but also there are video-based interventions that aim at increasing MHL [80] and students' help-seeking intentions [81] or at reducing stigma and enhancing help-seeking attitudes [82]. In addition to video-based interventions, even mobile apps can increase mental health literacy and reduce stigma [83].…”
Section: Implications For Practicementioning
confidence: 99%